Enchancing Safety Knowledge Through Digital Reading Modules for Oil And Gas Workers - Nugraha, Hendra; Jap, Gabriella; Purba, Hilarius Raditya Priambada (Asosiasi Ide Bahasa Kepri, 2024)
This study explores the development of English-language digital instructional modules tailored for personnel in the safety divisions of oil and gas industries. Focusing on the difficulties faced with English-language reading comprehension, the researchers crafted a comprehensive English instructional module, comprising the module content itself alongside ten varied quiz formats. Having been developed, the module was subjected to expert evaluation, with end-users offering insights into both the instructional content and quizzes during the implementation phase. Findings indicate that this digital format holds potential for field deployment; however, certain users continue to experience challenges in comprehending reading material while completing quizzes. Digital module developed also has easiness according to participants and therefore it can be developed further for another set of skills or different registers.